A temporoparietal infarct lesion presented as the first-episode mania in an elderly male (Indian Journal of Case Reports, 2024)
The occurrence of late-onset mania after 50 years of age for the 1st time is generally rare and is generally, but not necessarily, secondary to an organic lesion. Various underlying causes include neurological lesions, tumors, thyroid-related disorders, parathyroid abnormalities, electrolyte imbalances, and vascular lesions. After 75 years of age, the incidence of reported mania was 2/100,000, which is very rare. The main concern for such cases is to rule out secondary causes in assessment, diagnosis, and perspectives related to clinical management. We present a case where the first manic episode occurred at the age of 77 years with underlying infarcts in the temporal and parietal regions as seen in MRI brain contrast images.